Novel peptides with antioxidant and angiotensin converting enzyme inhibitory activity - Saari, Nazamid; Mohammad Zarei,; Ebrahimpour, Afshin; Abdul Hamid, Azizah; Abu Bakar, Fatimah (2013)
The present invention pertains to a process for manufacturing a proteolysate with antioxidant and Angiotensin converting enzyme (ACE) inhibitory properties, and to the isolate produced according the method of the invention. Therefore, furthermore is provided a method of identifying antioxidant and ACE inhibitory peptides from the proteolysate of the invention. The invention also relates to the peptides isolated using the screening method and the proteolysate of the invention. The products of the invention are particularly useful for the treatment of diseases associated with oxidative stress and/or diseases treatable with an ACE inhibitor, and thus can be used as medicines, or as food additives or supplements.